(3TQM JLQjO GdcdGe ddWhSjs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; aj EKHGJ GdUGfY hUaGJg hBKGQg hajg aUhd aj hLhOg GdehLhO Ef cGf hGLH agh hEdG GSJdReg GdGSJMGdI GdOhQ hGdJSdSds
(3BNQgG (B:s
(3SbW Yf GdBNQjf dCf YQVg JMUjd HPdc hEPG Xf cd WGFaI Cfg de jbe Hg GdBNQ CKe Gdcd HJQcg gPG BNQ eG JjSQ dfG Yf TQM JLQjO GdcdGes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3MSf GdHMQGfjs
Keywords: (3GdJhMjO hGdedd hGdfMds